1979
DOI: 10.3109/10826087909073938
|View full text |Cite
|
Sign up to set email alerts
|

Inhalant, Marijuana, and Alcohol Abuse among Barrio Children and Adolescents

Abstract: Prevalence of inhalant, marijuana, and alcohol abuse was studied in a sample of 457 male and female Mexican-American children and adolescents between the ages of 9 and 17 years. Subjects interviewed resided in four housing projects located in East Los Angeles. All interviews were conducted by adolescents who resided in the same housing projects. Results indicated that compared to a national sample, Mexican-American adolescents were at least 14 times more likely to be currently abusing inhalants. The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…Padilla et al (1979) compared the volatile solvent use rates of 457 Mexican-American youth in the barrio to volatile solvent use rates from a national sample--they found that volatile solvent users in barrios were more likely to have ever used volatile solvents, and are at least 14 times more likely to be currently using volatile solvents. Hispanics in poor barrio environments may use solvents heavily, but Hispanics in less stressful environments do not.…”
Section: Solvent Abuse Related Problemsmentioning
confidence: 98%
“…Padilla et al (1979) compared the volatile solvent use rates of 457 Mexican-American youth in the barrio to volatile solvent use rates from a national sample--they found that volatile solvent users in barrios were more likely to have ever used volatile solvents, and are at least 14 times more likely to be currently using volatile solvents. Hispanics in poor barrio environments may use solvents heavily, but Hispanics in less stressful environments do not.…”
Section: Solvent Abuse Related Problemsmentioning
confidence: 98%
“…Hispanic American studies, which have found substantially higher rates of inhalant use, were first published in the 1960s (see De la Rosa, Khalsa, & Rouser, 1990;and E. R. Padilla, A. M. Padilla, Morales, Olmedo, & Ramirez, 1979), but recent results show extreme variation by community (Mata & Andrew, 1988). Chavez and Swaim (1992) report that lifetime prevalence of use is no higher nationally among Hispanics than among non-Hispanic whites, but that current use of inhalants in the past month among Hispanic eighth graders is indeed higher.…”
Section: National Prevalence Across Age Groupsmentioning
confidence: 94%
“…The supply of available solvents is often a factor in experimentation, and solvent use provides a vicarious (substitute) high when intoxicants such as alcohol and other drugs are not available to these youths. This kind of experimentation may be more common in rural areas than in urban centers, although some localized ethnic neighborhoods may have problems as well (De la Rosa et al 1990;Padilla et al 1979). Such behaviors tend to be particularly more common in specific peer groups located in particular communities, neighborhoods, ethnic groups, and schools.…”
Section: Experimental Vicarious Youthful Usementioning
confidence: 96%
“…The choice of substances studied ranges from only narcotics (Amsel et al, 197 1 ;Joseph, 1973;Zahn and Ball, 1972) through a variety of licit and illicit "drugs'" (Crowther, 1972;Curtis and Simpson, 1976;Jimcnes, 1980;Page, 1980). Many studies include or focus upon alcohol use (Dembo et al,, 1979;Dembo et a[., 1979a;DiBartolarneo, 1980;Nuttall and Nuttall, 1981;Padilla et a!. , 1979;Perez et al, 1980) while others include cigarettes as well as alcohol (Guinn, 1975;Jackson, 1981; Downloaded by [University of Sussex Library] at 20:46 21 June 2016 ADOLESCEIVT SUBSTANCE ABUSE Kandel, Single, and Kessler, 1976;Robles, Martinez, and Moscoso, 1980).…”
Section: Review Of the Literaturementioning
confidence: 96%
“…, 1979;Perez et al, 1980) while others include cigarettes as well as alcohol (Guinn, 1975;Jackson, 1981; Downloaded by [University of Sussex Library] at 20:46 21 June 2016 ADOLESCEIVT SUBSTANCE ABUSE Kandel, Single, and Kessler, 1976;Robles, Martinez, and Moscoso, 1980). Inhalant abuse is also receiving attention, with a frequent focus on Mexican-American adolescents (Dworkin and Stephens, 1380;Padilla et al, 1979;Perez et al, 1980;Rubio, 1980;Stybel, Allen, and Lewis, 1976;Stybel, 1977).…”
Section: Review Of the Literaturementioning
confidence: 98%